Serbia's New Growth Agenda - World Bank (World Bank, Washington, DC, 2020)
Serbia is not growing as fast it could. Investment and productivity are low and slow growing; and the continuing large role of the state in the economy makes it difficult for the private sector to accelerate economic growth. Serbia is well-positioned to turn itself into a fast-growing, sophisticated modern economy, driven by its private sector. To succeed, Serbia needs a new strategy, a New Growth Agenda (NGA) to speed up growth, enable catch-up with its peers in Central and Eastern Europe and hasten convergence with the EU.